Predation of the round goby (Neogobius melanostomus Pallas, 1814) on Atlantic herring eggs in the Western Baltic Sea. Issue 9 (26th November 2018) - Wiegleb, Joschka; Kotterba, Paul; Hammer, Cornelius; Oesterwind, Daniel
ABSTRACT: The Ponto-Caspian round goby ( Neogobius melanostomus Pallas, 1814) is a prominent invasive species in many European waters. Eggs of the Western Baltic Spring Spawning Atlantic herring might be attractive prey for the invasive round goby during the spawning season. However, investigations of the small fish fauna in an important spawning area of herring, which was characterized by high densities of macrophytes, indicated a spatio-temporal mismatch of round goby and herring spawn in spring, at least on some of the known important spawning beds situated on vegetated sandy bottoms. In contrast, a spatio-temporal overlap between round gobies and herring spawn was observed in a more structured area, characterized with stones, where round gobies' stomachs were sampled. Further field study results suggest that large round gobies (> 10 cm) do not feed on herring eggs, while smaller round gobies (< 10 cm) do so. To support these results, we conducted laboratory feeding experiments with round gobies. When C. crangon, M. edulis and herring eggs were offered simultaneously, round gobies preferred C. crangon. M. edulis was preferred over herring eggs when C. crangon was absent. The predatory impact of the round goby on herring eggs seems to be of minor importance compared to other species, such as three-spined stickleback or perch. Applying the same data, different food 'preference indices' revealed a discrepancy in preference between indices. Therefore, we propose a modified food preference index (mE), taking into account four important parameters and combining benefits of two commonly applied indices.